ACUTE ENTERIC INFECTIONS IN CHILDREN IN IRKUTS REGION - E. V. Anganova (Detskie Infekcii (Moskva), 2015)
The analysis of the incidence of acute intestinal infections in children was carried out in Irkutsk region. The study demonstrated significant increase of the incidence of acute intestinal infections in Irkutsk region and revealed exceedance of all-Russia indicators. It is established that bacterial intestinal infections dominate. Among the bacterial pathogens of acute intestinal infections dominated opportunistic bacteria of the family Enterobacteriaceae. The Analysis also revealed the change of quantitative composition in the long-term aspect, and a significant increase in the proportion of bacteria of the genus Klebsiella. Etiological structure of acute enteric infections in children in recent years has changed. The proportion of viruses has increased. The viral infection has had higher growth rate in comparison with bacterial infections.